Development of the Warwick Axial Spondyloarthritis faTigue and Energy questionnaire (WASTEd)—a new patient-reported outcome measure. Issue 1 (4th April 2022) - Pearson, Nathan A; Tutton, Elizabeth; Martindale, Jane; Strickland, George; Thompson, Jean; Packham, Jonathan C; Creamer, Paul; Haywood, Kirstie L
Abstract: Objective: The aim was to co-produce and test a potential new patient-reported outcome measure (PROM), the Warwick Axial Spondyloarthritis faTigue and Energy questionnaire (WASTEd), providing vital qualitative confirmation of conceptual relevance, clarity and acceptability. Methods: Informed by measurement theory, we collaborated with patient partners throughout a three-stage, iterative process of PROM development. In stage 1, informed by patient interviews, reviews exploring patients' fatigue experiences and existing PROMs of fatigue, an initial measurement framework of axial spondyloarthritis (axSpA) fatigue and energy and candidate items were defined. In stage 2, the relevance and acceptability of the measurement framework and candidate items were assessed qualitatively by focus group participants. In stage 3, patients participated in pre-testing interviews to assess item comprehensiveness, relevance, acceptability and comprehensibility. Results: Stage 1 informed the development of an initial five-domain measurement framework with 59 candidate items. In stage 2, five patients and seven health-care professionals participated in four focus groups to derive a 40-item model of fatigue and energy. Collaborative engagement with patient research partners supported refinement of questionnaire structure and content further. Pre-testing with ten patients across two interview rounds in stage 3 produced a four-domain, 30-item long-form questionnaire. Conclusion: An active collaboration with patients and health-care professionals has supported the co-production of a potential new PROM of axSpA fatigue, underpinned by strong evidence of face and content validity. The WASTEd extends the assessment of fatigue beyond severity, highlighting the importance of symptom frequency, energy and self-management. Future research will involve psychometric evaluation, supporting item reduction, structural refinement and confirmation of PROM validity.